Battling "the bane of our cities": Class, territory, and the prohibition debate in Toronto, 1877 - Sendbuehler, M. (Urban History Review / Revue d'histoire urbaine, 1993)
In the nineteenth century, the tavern was an important institution in urban working-class life. Because of the social ills associated with alcohol abuse and public drinking, there were frequent attempts to lessen the tavern's importance or to eliminate it entirely. This paper examines several tavern-related issues that emerged in Toronto in the 1870s and 1880s. The Crooks Act, passed in 1876, employed powerful measures to deal with political and temperance questions simultaneously. The intersection of class, politics, temperance, and urban life led to a territorial solution to the liquor question. These issues were dealt with by the people of Toronto in 1877, when they declined to prohibit public drinking in the city via the Dunkin Act, a local option prohibition statute of the Province of Canada.